1992
DOI: 10.1001/archsurg.1992.01420030043008
|View full text |Cite
|
Sign up to set email alerts
|

Groin Dissection in the Treatment of Lower-Extremity Melanoma Short-term and Long-term Morbidity

Abstract: Groin dissection was performed in 151 consecutive patients from 1970 to 1984. Groin dissections were therapeutic in 138 cases (91%) and elective in 13 (9%). One hundred forty-three patients (95%) underwent an ilioinguinal node dissection, while eight (5%) were treated with an inguinal node dissection. In 88 patients, the groin dissection was combined with isolated regional perfusion. Primary wound closure was performed in 140 patients (93%). There was no 30-day postoperative mortality. Complications included t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
63
1
10

Year Published

1993
1993
2015
2015

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 116 publications
(79 citation statements)
references
References 9 publications
5
63
1
10
Order By: Relevance
“…16,18,20,22,[26][27][28] Two studies used water displacement methods exclusively for limb volume assessment, defining lymphedema thresholds of 6.5% and 10%, 29,30 and another 4 studies used both circumference and water displacement. 23,[31][32][33] More subjective assessments of lymphedema included the Common Toxicity Criteria and the Late Effects Normal Tissues Scales, 34,35 but the majority used ad hoc clinical grading to define lymphedema such as skin-pinch tests or scales defined by the treating physician. Global comparisons revealed that patients were 91% more likely to be identified with lymphedema (relative risk, 1.91; 95% confidence interval [CI], 1.71-2.12; P < .001) when they were enrolled in studies using objective measurement methods (ie, volume and circumference measures) than those enrolled in studies using subjective (eg, self-report or provider observation) assessments.…”
Section: Methods Of Lymphedema Assessmentmentioning
confidence: 99%
“…16,18,20,22,[26][27][28] Two studies used water displacement methods exclusively for limb volume assessment, defining lymphedema thresholds of 6.5% and 10%, 29,30 and another 4 studies used both circumference and water displacement. 23,[31][32][33] More subjective assessments of lymphedema included the Common Toxicity Criteria and the Late Effects Normal Tissues Scales, 34,35 but the majority used ad hoc clinical grading to define lymphedema such as skin-pinch tests or scales defined by the treating physician. Global comparisons revealed that patients were 91% more likely to be identified with lymphedema (relative risk, 1.91; 95% confidence interval [CI], 1.71-2.12; P < .001) when they were enrolled in studies using objective measurement methods (ie, volume and circumference measures) than those enrolled in studies using subjective (eg, self-report or provider observation) assessments.…”
Section: Methods Of Lymphedema Assessmentmentioning
confidence: 99%
“…The finding of a positive SLN identify patients who might benefit from completion lymph node dissection (CLND) [4]. However, CLND carries significant morbidity [5] and [6] and there is no consensus on the benefit of a completion dissection in melanoma patients. In fact reports in the literature showed that only from 14 to 28% [7], [8], [9], [10] and [11] of positive patients will harbour further disease in the affected basin.…”
Section: Introductionmentioning
confidence: 99%
“…The pelvic nodes were approached extraperitoneally through a lower abdominal wall incision following the technique described by Baas et al 23 Axillary dissection comprised dissection of levels I-III.…”
Section: Radical Lymph Node Dissectionmentioning
confidence: 99%